Bulgaria : 2022 Article IV Consultation - Press Release; and Staff Report for Bulgaria. (IMF Staff Country Reports; Country Report ;, 2022)
The economy showed resilience through the pandemic, but the war in Ukraine has clouded the outlook, heightened uncertainty, and increased downside risks. With policy support, growth rebounded in 2021 despite the lingering COVID-19 crisis and protracted political uncertainty that hampered investment. Inflation accelerated significantly, pushed by global factors and strong domestic consumption. GDP growth is projected to slow below 3 percent and average inflation to exceed 12 percent in 2022. In this context, policies must navigate difficult trade-offs as they need to support activity, meet needs from the war, and contain inflation, while raising living standards, reducing inequalities, and supporting the green transition.